6.102 Problems 10101 to 10200

Table 6.203: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

10101

\[ {}y^{\prime }-\frac {y a f \left (x^{c} y\right )+c \,x^{a} y^{b}}{x b f \left (x^{c} y\right )-x^{a} y^{b}} = 0 \]

10102

\[ {}2 y^{\prime }-3 y^{2}-4 a y-b -c \,{\mathrm e}^{-2 a x} = 0 \]

10103

\[ {}x y^{\prime }-\sqrt {a^{2}-x^{2}} = 0 \]

10104

\[ {}x y^{\prime }+y-x \sin \left (x \right ) = 0 \]

10105

\[ {}x y^{\prime }-y-\frac {x}{\ln \left (x \right )} = 0 \]

10106

\[ {}x y^{\prime }-y-x^{2} \sin \left (x \right ) = 0 \]

10107

\[ {}x y^{\prime }-y-\frac {x \cos \left (\ln \left (\ln \left (x \right )\right )\right )}{\ln \left (x \right )} = 0 \]

10108

\[ {}x y^{\prime }+a y+b \,x^{n} = 0 \]

10109

\[ {}x y^{\prime }+y^{2}+x^{2} = 0 \]

10110

\[ {}x y^{\prime }-y^{2}+1 = 0 \]

10111

\[ {}x y^{\prime }+y^{2} a -y+b \,x^{2} = 0 \]

10112

\[ {}x y^{\prime }+y^{2} a -b y+c \,x^{2 b} = 0 \]

10113

\[ {}x y^{\prime }+y^{2} a -b y-c \,x^{\beta } = 0 \]

10114

\[ {}x y^{\prime }+x y^{2}+a = 0 \]

10115

\[ {}x y^{\prime }+x y^{2}-y = 0 \]

10116

\[ {}x y^{\prime }+x y^{2}-y-a \,x^{3} = 0 \]

10117

\[ {}x y^{\prime }+x y^{2}-\left (2 x^{2}+1\right ) y-x^{3} = 0 \]

10118

\[ {}x y^{\prime }+a x y^{2}+2 y+b x = 0 \]

10119

\[ {}x y^{\prime }+a x y^{2}+b y+c x +d = 0 \]

10120

\[ {}x y^{\prime }+x^{a} y^{2}+\frac {\left (a -b \right ) y}{2}+x^{b} = 0 \]

10121

\[ {}x y^{\prime }+a \,x^{\alpha } y^{2}+b y-c \,x^{\beta } = 0 \]

10122

\[ {}x y^{\prime }-y^{2} \ln \left (x \right )+y = 0 \]

10123

\[ {}x y^{\prime }-y \left (-1+2 y \ln \left (x \right )\right ) = 0 \]

10124

\[ {}x y^{\prime }+f \left (x \right ) \left (y^{2}-x^{2}\right )-y = 0 \]

10125

\[ {}x y^{\prime }+y^{3}+3 x y^{2} = 0 \]

10126

\[ {}x y^{\prime }-\sqrt {x^{2}+y^{2}}-y = 0 \]

10127

\[ {}x y^{\prime }+a \sqrt {x^{2}+y^{2}}-y = 0 \]

10128

\[ {}x y^{\prime }-x \sqrt {x^{2}+y^{2}}-y = 0 \]

10129

\[ {}x y^{\prime }-x \left (y-x \right ) \sqrt {x^{2}+y^{2}}-y = 0 \]

10130

\[ {}x y^{\prime }-x \,{\mathrm e}^{\frac {y}{x}}-y-x = 0 \]

10131

\[ {}x y^{\prime }-y \ln \left (y\right ) = 0 \]

10132

\[ {}x y^{\prime }-y \left (\ln \left (x y\right )-1\right ) = 0 \]

10133

\[ {}x y^{\prime }-y \left (x \ln \left (\frac {x^{2}}{y}\right )+2\right ) = 0 \]

10134

\[ {}x y^{\prime }-\sin \left (x -y\right ) = 0 \]

10135

\[ {}x y^{\prime }+\left (\sin \left (y\right )-3 x^{2} \cos \left (y\right )\right ) \cos \left (y\right ) = 0 \]

10136

\[ {}x y^{\prime }-\sin \left (\frac {y}{x}\right ) x -y = 0 \]

10137

\[ {}x y^{\prime }+x \cos \left (\frac {y}{x}\right )-y+x = 0 \]

10138

\[ {}x y^{\prime }+x \tan \left (\frac {y}{x}\right )-y = 0 \]

10139

\[ {}x y^{\prime }-y f \left (x y\right ) = 0 \]

10140

\[ {}x y^{\prime }-y f \left (x^{a} y^{b}\right ) = 0 \]

10141

\[ {}x y^{\prime }+a y-f \left (x \right ) g \left (x^{a} y\right ) = 0 \]

10142

\[ {}\left (1+x \right ) y^{\prime }+y \left (y-x \right ) = 0 \]

10143

\[ {}2 x y^{\prime }-y-2 x^{3} = 0 \]

10144

\[ {}\left (2 x +1\right ) y^{\prime }-4 \,{\mathrm e}^{-y}+2 = 0 \]

10145

\[ {}3 x y^{\prime }-3 x \ln \left (x \right ) y^{4}-y = 0 \]

10146

\[ {}x^{2} y^{\prime }+y-x = 0 \]

10147

\[ {}x^{2} y^{\prime }-y+x^{2} {\mathrm e}^{x -\frac {1}{x}} = 0 \]

10148

\[ {}x^{2} y^{\prime }-\left (x -1\right ) y = 0 \]

10149

\[ {}x^{2} y^{\prime }+y^{2}+x y+x^{2} = 0 \]

10150

\[ {}x^{2} y^{\prime }-y^{2}-x y = 0 \]

10151

\[ {}x^{2} y^{\prime }-y^{2}-x y-x^{2} = 0 \]

10152

\[ {}x^{2} \left (y^{\prime }+y^{2}\right )+a \,x^{k}-b \left (b -1\right ) = 0 \]

10153

\[ {}x^{2} \left (y^{\prime }+y^{2}\right )+4 x y+2 = 0 \]

10154

\[ {}x^{2} \left (y^{\prime }+y^{2}\right )+a x y+b = 0 \]

10155

\[ {}x^{2} \left (y^{\prime }-y^{2}\right )-a \,x^{2} y+a x +2 = 0 \]

10156

\[ {}x^{2} \left (y^{\prime }+y^{2} a \right )-b = 0 \]

10157

\[ {}x^{2} \left (y^{\prime }+y^{2} a \right )+b \,x^{\alpha }+c = 0 \]

10158

\[ {}x^{2} y^{\prime }+a y^{3}-a \,x^{2} y^{2} = 0 \]

10159

\[ {}x^{2} y^{\prime }+x y^{3}+y^{2} a = 0 \]

10160

\[ {}x^{2} y^{\prime }+a \,x^{2} y^{3}+b y^{2} = 0 \]

10161

\[ {}\left (x^{2}+1\right ) y^{\prime }+x y-1 = 0 \]

10162

\[ {}\left (x^{2}+1\right ) y^{\prime }+x y-x \left (x^{2}+1\right ) = 0 \]

10163

\[ {}\left (x^{2}+1\right ) y^{\prime }+2 x y-2 x^{2} = 0 \]

10164

\[ {}\left (x^{2}+1\right ) y^{\prime }+\left (1+y^{2}\right ) \left (2 x y-1\right ) = 0 \]

10165

\[ {}\left (x^{2}+1\right ) y^{\prime }+x \sin \left (y\right ) \cos \left (y\right )-x \left (x^{2}+1\right ) \cos \left (y\right )^{2} = 0 \]

10166

\[ {}\left (x^{2}-1\right ) y^{\prime }-x y+a = 0 \]

10167

\[ {}\left (x^{2}-1\right ) y^{\prime }+2 x y-\cos \left (x \right ) = 0 \]

10168

\[ {}\left (x^{2}-1\right ) y^{\prime }+y^{2}-2 x y+1 = 0 \]

10169

\[ {}\left (x^{2}-1\right ) y^{\prime }-y \left (y-x \right ) = 0 \]

10170

\[ {}\left (x^{2}-1\right ) y^{\prime }+a \left (y^{2}-2 x y+1\right ) = 0 \]

10171

\[ {}\left (x^{2}-1\right ) y^{\prime }+a x y^{2}+x y = 0 \]

10172

\[ {}\left (x^{2}-1\right ) y^{\prime }-2 x y \ln \left (y\right ) = 0 \]

10173

\[ {}\left (x^{2}-4\right ) y^{\prime }+\left (x +2\right ) y^{2}-4 y = 0 \]

10174

\[ {}\left (x^{2}-5 x +6\right ) y^{\prime }+3 x y-8 y+x^{2} = 0 \]

10175

\[ {}\left (x -a \right ) \left (x -b \right ) y^{\prime }+y^{2}+k \left (y+x -a \right ) \left (y+x -b \right ) = 0 \]

10176

\[ {}2 x^{2} y^{\prime }-2 y^{2}-x y+2 x \,a^{2} = 0 \]

10177

\[ {}2 x^{2} y^{\prime }-2 y^{2}-3 x y+2 x \,a^{2} = 0 \]

10178

\[ {}x \left (2 x -1\right ) y^{\prime }+y^{2}-\left (4 x +1\right ) y+4 x = 0 \]

10179

\[ {}2 x \left (x -1\right ) y^{\prime }+\left (x -1\right ) y^{2}-x = 0 \]

10180

\[ {}3 x^{2} y^{\prime }-7 y^{2}-3 x y-x^{2} = 0 \]

10181

\[ {}3 \left (x^{2}-4\right ) y^{\prime }+y^{2}-x y-3 = 0 \]

10182

\[ {}\left (a x +b \right )^{2} y^{\prime }+\left (a x +b \right ) y^{3}+c y^{2} = 0 \]

10183

\[ {}x^{3} y^{\prime }-y^{2}-x^{4} = 0 \]

10184

\[ {}x^{3} y^{\prime }-y^{2}-x^{2} y = 0 \]

10185

\[ {}x^{3} y^{\prime }-y^{2} x^{4}+x^{2} y+20 = 0 \]

10186

\[ {}x^{3} y^{\prime }-y^{2} x^{6}-\left (2 x -3\right ) x^{2} y+3 = 0 \]

10187

\[ {}x \left (x^{2}+1\right ) y^{\prime }+x^{2} y = 0 \]

10188

\[ {}x \left (x^{2}-1\right ) y^{\prime }-\left (2 x^{2}-1\right ) y+a \,x^{3} = 0 \]

10189

\[ {}x \left (x^{2}-1\right ) y^{\prime }+\left (x^{2}-1\right ) y^{2}-x^{2} = 0 \]

10190

\[ {}x^{2} \left (x -1\right ) y^{\prime }-y^{2}-x \left (x -2\right ) y = 0 \]

10191

\[ {}2 x \left (x^{2}-1\right ) y^{\prime }+2 \left (x^{2}-1\right ) y^{2}-\left (3 x^{2}-5\right ) y+x^{2}-3 = 0 \]

10192

\[ {}3 x \left (x^{2}-1\right ) y^{\prime }+x y^{2}-\left (x^{2}+1\right ) y-3 x = 0 \]

10193

\[ {}\left (a \,x^{2}+b x +c \right ) \left (x y^{\prime }-y\right )-y^{2}+x^{2} = 0 \]

10194

\[ {}x^{4} \left (y^{\prime }+y^{2}\right )+a = 0 \]

10195

\[ {}x \left (x^{3}-1\right ) y^{\prime }-2 x y^{2}+y+x^{2} = 0 \]

10196

\[ {}\left (2 x^{4}-x \right ) y^{\prime }-2 \left (x^{3}-1\right ) y = 0 \]

10197

\[ {}\left (a \,x^{2}+b x +c \right )^{2} \left (y^{\prime }+y^{2}\right )+A = 0 \]

10198

\[ {}x^{7} y^{\prime }+2 \left (x^{2}+1\right ) y^{3}+5 y^{2} x^{3} = 0 \]

10199

\[ {}x^{n} y^{\prime }+y^{2}-\left (n -1\right ) x^{n -1} y+x^{2 n -2} = 0 \]

10200

\[ {}x^{n} y^{\prime }-y^{2} a -b \,x^{2 n -2} = 0 \]